Profile of the Implementation of Discovey Learning Model in Science Learning - Mahyuddin Syaifulloh; Sifak Indana; Rudiana Agustini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Research was conducted to describe and analyze the implementation of discovery learning model of science learning in Indonesia. This research method uses qualitative methods with using secondary data. The sample in this research is 30 articles published in international and national journals. Based on the analysis of 30 articles on science learning using discovery learning model in Indonesia, it can be seen that the discovery learning model has a positive impact on student learning outcomes, it can improve students' critical thinking skills, students' science process skills, students' scientific literacy, aspects of problem solving skills, and also students' understanding of concepts. there are also several disadvantages of the discovery learning model, there are; it will be optimal if it combine with media or other methods, students will be confused if they do not get the instruction from the teacher, and it require a lot of preparation and learning duration. Based on the literature review of the implementation of the discovery learning model in 2012-2021 that has been carried out, it can be concluded that the discovery learning model has a positive impact on science learning.